2021
DOI: 10.1101/2021.11.06.467542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Imp and Syp RBPs in precise neuronal elimination by apoptosis through the regulation of TFs

Abstract: SUMMARYNeuronal stem cells produce a finite and stereotyped number of neuronal progenies. This process must be finely regulated during development and adult stages to ensure proper brain function. In Drosophila, stem cells, called Neuroblasts, produce an invariant number of neurons. Two RNA binding proteins, Imp and Syp, play a central role in controlling the speed of division and the end of the proliferative phase of individual NBs, two parameters that influences the final number of neurons produced. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 68 publications
(135 reference statements)
1
4
0
Order By: Relevance
“…To investigate further post-transcriptional regulation, we investigated the expression dynamics and function on muscle innervation of two known RBPs, Imp and Syp, that are major players in the temporal specification of VNC and central brain lineages in Drosophila (Liu et al, 2015;Ren et al, 2017;Syed et al, 2017). In Lin A/15 NB, both Imp and Syp proteins follow opposing temporal expression gradients in accordance with previously described studies of other NBs in the CNS (Guan et al, 2021).…”
Section: Opposite Spatial Gradients Of Imp and Syp Control The Specif...supporting
confidence: 57%
See 4 more Smart Citations
“…To investigate further post-transcriptional regulation, we investigated the expression dynamics and function on muscle innervation of two known RBPs, Imp and Syp, that are major players in the temporal specification of VNC and central brain lineages in Drosophila (Liu et al, 2015;Ren et al, 2017;Syed et al, 2017). In Lin A/15 NB, both Imp and Syp proteins follow opposing temporal expression gradients in accordance with previously described studies of other NBs in the CNS (Guan et al, 2021).…”
Section: Opposite Spatial Gradients Of Imp and Syp Control The Specif...supporting
confidence: 57%
“…However, both proteins might also determine other aspects of MN fate. In our parallel study, we have demonstrated that both RBPs act in iMNs to determine the survival of Lin A/15 MNs (Guan et al, 2021). Syp prevents the survival of iMNs, whereas Imp promotes it.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations